Dimensionamento da perna barométrica de uma coluna de flotação aplicado à melhoria na estabilidade do processo - Alexandre Camilo Leles de Figueiredo (2019)
The inefficiency in controlling the slurry/froth interface level of the scavenger column stage can severely impair the process performance of a flotation circuit, such as that operated at Samarco, which had the iron content in the tailings reaching levels above 20% and, consequently, not meeting the company’s iron recovery and pellet feed production targets. Therefore, the present work aimed to present a new dimensional design of the flotation column slurry/froth interface level control system. This control is achieved by the automated opening and closing of the valve installed in the barometric leg of the flotation column discharge, manipulating the non-floated flow rate. Two expressions for the dimensional design were developed based on predefined equipment installation criteria and classic Fluid Mechanics models (equations for the steady motion of a real fluid and the estimation of head losses in pipes). From the sampling and the elaboration of a mass balance, the main process parameters necessary for the dimensional design were obtained: particle size distribution of the flotation column feed material (d10=3.3μm, d50=20.0μm, d60=26.0μm e d95=75.0μm), solids specific gravity (3800kg/m3), slurry density (1390kg/m3), volumetric solids concentration (13.8%), dynamic viscosity of the slurry (1.7×10-3kg/m.s) and slurry flow rate to be transferred as concentrate to the subsequent stage (219.5m3/h). Hydraulic calculations were performed and showed that the installed 6” (15.24cm) diameter tubes and control system valve were appropriate. However, it was necessary to reduce the barometric leg horizontal stretch length from 14.6m to 1.9m and the barometric leg height from 4.6m to 2.6m. The barometric leg adequacy, performed at a scheduled stoppage of the flotation circuit, considerably decreased the variability in controlling the slurry/froth interface level, reduced the iron content in the tailings from 24.9% to 18.9% and, consequently, increased the iron recovery in the flotation stage from 97.9% to 98.7%, without negatively impairing the main circuit quality indicator which is the silica content in the concentrate.